Shakespeare and the Performance of Girlhood - Williams, D. author. aut Link
XI, 277 p.
Keywords: This is the first scholarly study devoted to Shakespeare's girl characters and conceptions of girlhood. It charts the development of Shakespeare's treatment of the girl as a dramatic and literary figure, and explores the impact of Shakespeare's girl characters on the history of early modern girls as performers, patrons, and authors.